Theoretical Studies on the Reaction Mechanism of Photocatalytic Degradation of Ethylene in Gas Phase Over TiO2 - Min Bi, Hui; Ping Hu, Jun; Tao Xie, Peng; Quan Chai, Xing; Liu, Yan; Ying You, Fu (Asian Journal of Chemistry, 2012)
The reaction mechanism of photocatalytic degradation of ethylene in gas phase over titanium dioxide (TiO2) was investigated by using B3LYP methods with the 6-311G basis sets and reaction channels were found. Geometries of the reactants predicted that the intermediates with the structure of hydrogen bonds, last products of reaction is CO2 and H2O. Intermediates and products were optimized and frequency were carried out. The calculated results successfully explained the conclusion of Huang Yali's experimental study. From the view of energy analysis, the reaction is a process to reduce energy, the reaction can be carried out under mild conditions from the theoretical studies. This will be helpful for the experimental research of the photocatalytic degradation of ethylene in gas phase.